The Impact of Recession on the Distribution of Annual Unemployment - Beach, Charles; Kaliski, S.F. (Relations industrielles / Industrial Relations, 1986)
The authors use microdata from the Canadian Annual Work Patterns Survey for 1978, 1980 and 1982 to compare the distributions of the annual unemployment experiences of persons.